2012
DOI: 10.1007/s10620-012-2097-4
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid Plus Pentoxifylline Is Not Better than Corticosteroid Alone for Improving Survival in Severe Alcoholic Hepatitis (COPE Trial)

Abstract: For patients with severe alcoholic hepatitis, a combination of corticosteroids and pentoxifylline has no additional survival advantage compared with corticosteroids alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 32 publications
1
42
0
2
Order By: Relevance
“…As a result of the poor quality of most of the studies, the authors concluded that no conclusions could be drawn regarding whether pentoxifylline had a positive, negative, or neutral effect on participants with alcoholic hepatitis. Mathurin et al 6 found no evidence of an additive effect when pentoxifylline was added to prednisolone confirming the findings of the COPE trial 7 . Based on these published randomized controlled trials (RCT) and meta-analyses, prednisolone and pentoxifylline were incorporated in the past 5 years into guidelines of the American Association for the Study of Liver Disease (AASLD) and the European Association for the Study of the Liver (EASL) 8,9 but these recommendations remained controversial due to the quality of the data upon which they were based.…”
Section: Discussionmentioning
confidence: 74%
“…As a result of the poor quality of most of the studies, the authors concluded that no conclusions could be drawn regarding whether pentoxifylline had a positive, negative, or neutral effect on participants with alcoholic hepatitis. Mathurin et al 6 found no evidence of an additive effect when pentoxifylline was added to prednisolone confirming the findings of the COPE trial 7 . Based on these published randomized controlled trials (RCT) and meta-analyses, prednisolone and pentoxifylline were incorporated in the past 5 years into guidelines of the American Association for the Study of Liver Disease (AASLD) and the European Association for the Study of the Liver (EASL) 8,9 but these recommendations remained controversial due to the quality of the data upon which they were based.…”
Section: Discussionmentioning
confidence: 74%
“…In a study comparing pentoxifylline with corticosteroids, a benefi t in survival in the pentoxifylline group was observed, with 15 % 1-month mortality in pentoxifylline-treated patients vs. 35 % mortality in patients treated with corticosteroids [ 110 ]. In a second study, in which a combination of pentoxifylline and corticosteroids was compared with corticosteroids alone, no difference in survival was found; however, this study was not double-blind in design [ 111 ]. Experimental data have demonstrated the anti-infl ammatory and antitumor necrosis factor alpha effects of pentoxifylline [ 112 ], although its benefi t in severe alcoholic hepatitis seems to be related to the prevention of hepatorenal syndrome [ 103 , 109 ].…”
Section: Pentoxifyllinementioning
confidence: 92%
“…23,24 Three small studies [25][26][27] have compared steroids directly with PTX but the results were inconsistent. One study 28 explored the use of PTX as a rescue therapy once steroids had failed to improve liver function tests (LFTs) but this strategy did not influence survival.…”
Section: Steroids And/or Pentoxifyllinementioning
confidence: 99%